Genome-wide analysis of the snakin/GASA gene family in solanum tuberosum cv. Kennebec - Nahirñak, Vanesa; Rivarola, Maximo Lisandro; Gonzalez De Urreta, Martin Salvador; Paniego, Norma Beatriz; Hopp, Horacio Esteban; Almasia, Natalia Ines; Vazquez Rovere, Cecilia (2017)
Snakin/GASA proteins have been involved in different aspects of plant growth and development although their exact role is still intriguing. All of them maintain 12 cysteines of the C-terminus in highly conserved positions that are responsible for their structure and are essential for their biochemical activity as antioxidants. Two members were isolated from Solanum tuberosum to date (Snakin-1 and Snakin-2) and were shown to have antimicrobial activity. We have recently demonstrated that Snakin-1 has additional roles in plant growth and development. We carried out a genome-wide search for new Snakin/GASA family members in potato. 16 Snakin/GASA genes were isolated, sequenced and characterized. Interestingly, we found in Solanum tuberosum subsp. tuberosum cv. Kennebec that Snakin-1, Snakin-2 and Snakin-3 expression is affected by bacterial and/or fungal inoculation. These results strengthen the participation of Snakin-1 and Snakin-2 genes in biotic stress tolerance and suggest that Snakin-3 is also involved in plant defense. The data presented here could be a good starting point for more focused and deep investigations regarding the biological functions of potato Snakin/GASA genes during plant development and in response to environmental stress.